Smart-ICT for weather and water information and advice to smallholders in Africa - Amarnath, Giriraj; Simons, G.; Sharma, Bharat R.; Mohammed, Y.; Gismalla, Y.; Smakhtin, Vladimir U. (2013)
Climate change, water scarcity and food security are becoming increasingly important topics for the growing population of Africa. Due to a general lack of water resources in semi-arid and arid zones, water is an increasingly scarce input in agriculture. The impact of climate change exacerbates this situation further. Even in areas with abundant water resources, optimal use is hampered by insufficient infrastructure to capture these resources and knowledge on appropriate use. With the increased demand and competition for limited water resources the challenge is to increase agricultural production while reducing water consumption ("more crop per drop"). Solutions must be found to enable rural people to overcome poverty, and a start can be made by assisting in food production and water management to combat food insecurity. Local solutions must be adopted in which rural people's access to new technologies increases. Therefore, smart and affordable technologies need to be adapted to customize farm management for this group of African farmers. Poor farmers need to access real-time information, be able to exchange and apply it: smart ICT (e.g. cell-phones backed up by the web) can play a fundamental role in the communication process.